(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Gender equality is a key principle in healthcare, ensuring equal access and rights to medical services for all individuals, particularly women. Despite growing attention to women’s health in recent years, significant disparities and barriers still persist in many parts of the world. This article provides a comprehensive analysis of the current global state of women’s health, exploring the root causes of gender disparities, the impact of cultural and social factors, and biases within medical research and clinical care. The study draws on data from WHO, UN Women, and other international sources. It also outlines policy recommendations and strategies for strengthening gender-responsive healthcare systems and legal protections for women worldwide.